USA trade policy agenda perspectives in international trade - Marcel Kordos (Institute of Economic Research (IER), 2017)
International trade means the exchange of goods or services along international borders. This type of trade allows for a greater competition and more competitive pricing in the market. Probably the most important single insight in all of international economics is that there are gains from trade - that is, when countries sell goods and services to each other, this exchange is almost always to their mutual benefit. Importing and exporting of goods is big business in today's global economy thus international trade is supposed to be beneficial for a particular economy even for the USA. The question is arising if Americans shouldn't buy American goods whenever possible, to help create jobs in the United States. Paper deals with issues such as the U.S. international trade characteristics in terms of territorial and commodity structure, the U.S. export trade promotion strategy, the impact of trade on the US economy and international trade development as well as President's Obama strategy regarding the U.S. international trade strategy. This study is analyzing the US trade policy agenda and discussing the impact of foreign trade on the U.S. economy and its current status in international economic relations. To accomplish this goal, methods such as analysis, comparison, synthesis and logical deduction are to be used; facts from scientific and professional publications, periodical and non-periodical press. International trade of the United States is one of the world's most significant economic markets. The country is among the top three global importers and exporters. USA has trade relations with many other countries. Through efficiency, competition, and relationships the international trade can increase economic growth and allow for all countries to benefit from it.
Keywords: F19; F59; F63; 330; competitiveness enhancement; export promotion strategy; international economics; jobs creation